(untitled) (Journal of Engineering, 2020)
Thin-walled members are increasingly used in structural applications, especially in light structures like in constructions and aircraft structures because of their high strength-to-weight ratio. Perforations are often made on these structures for reducing weight and to facilitate the services and maintenance works like in aircraft wing ribs. This type of structures suffers from buckling phenomena due to its dimensions, and this suffering increases with the presence of holes in it. This study investigated experimentally and numerically the buckling behavior of aluminum alloy 6061-O thin-walled lipped channel beam with specific holes subjected to compression load. A nonlinear finite elements analysis was used to obtain the buckling loads of the beams. Experimental tests were done to validate the finite element results. Three factors namely; shape of holes, opening ratio D/Do and the spacing ratio S/Do were chosen to study their effects on the buckling strength of the channel beams. Finite elements results were obtained by using Taguchi method to identify the best combination of the three parameters for optimum critical buckling load, whereas determining the contribution of each parameter on buckling strength was implemented by using the analysis of variance technique (ANOVA) method. Results showed that the combination of parameters that gives the best buckling strength is the hexagonal hole shape, D/Do=1.7 and S/Do= 1.3 and the opening ratio (or size of holes) is the most effective on buckling behavior.